A study on the benefits of outsourcing in the production process of the mechanical industry - Ueberson, Fábio Fernandes; Carrino, Adauto Luiz (Seven Editora, 2024)
The practice of outsourcing dates back to the Industrial Revolution, gaining prominence in the 20th century due to organizations’ relentless pursuit of efficiency and cost reduction. In Brazil, this trend became prominent in the last decades, especially from the 1990s onwards, driven by changes in labor laws. There has been a noticeable increase in outsourcing various activities, from administrative services to strategic functions. This phenomenon is complex, generating debates about its social and economic impacts. However, the crucial importance of effective management of contracts and relationships with suppliers to ensure strategic alignment and quality of the final product stands out. Nevertheless, this work proposes the respective problematization with the question: What are some of the possible benefits of outsourcing in the production process of the mechanical industry? To achieve answers to this problem, we outline as a general objective to demonstrate some of the possible benefits of outsourcing in the production process of the mechanical industry. Regarding the methodological procedure, we undertake a brief literature review, with developments in qualitative classification information, thus constituting some theoretical contexts that contributed to achieving the established objective. The results indicate that when well-managed, outsourcing can generate efficiency and competitiveness. However, it is emphasized the importance of a balance between the interests of companies and the protection of labor rights. It is concluded that outsourcing, when carried out with caution and responsibility, can be an effective strategy to reduce operations, but the safeguarding of workers’ rights should be prioritized. DOI:https://doi.org/10.56238/sevened2024.010-053